Application of biomass pyrolytic polygeneration technology using retort reactors. (January 2016) - Yang, Haiping; Liu, Biao; Chen, Yingquan; Chen, Wei; Yang, Qing; Chen, Hanping
Highlights: The commercial biomass pyrolytic polygeneration using retort reactor work well. Biogas is enriched CH4 and H2 and its LHV reach 12 MJ/m 3, used as gaseous fuel. Phenol and acetic acid is the major organic composition in woody tar and vinegar. The char product had a high LHV (31 MJ/kg) and solid fuel properties. The net economic income of commercial factory is 577, 500 yuan RMB. Abstract: To introduce application status and illustrate the good utilisation potential of biomass pyrolytic polygeneration using retort reactors, the properties of major products and the economic viability of commercial factories were investigated. The capacity of one factory was about 3000 t of biomass per year, which was converted into 1000 t of charcoal, 950, 000 Nm 3 of biogas, 270 t of woody tar, and 950 t of woody vinegar. Charcoal and fuel gas had LHV of 31 MJ/kg and 12 MJ/m 3, respectively, indicating their potential for use as commercial fuels. The woody tar was rich in phenols, while woody vinegar contained large quantities of water and acetic acid. The economic analysis showed that the factory using this technology could be profitable, and the initial investment could be recouped over the factory lifetime. This technology offered a promising means of converting abundant agricultural biomass into high-value products.